CENTRAL BANK LOAN TO ISLAMIC BANK (LIQUDITY CASE STUDY) - Ahmad Aswan Waruwu; Saparuddin Siregar (Proceeding International Seminar of Islamic Studies, 2023)
Purpose of writing this articleiadalahito analyze Liquidity Risk Management in Islamic Banking. This type of research includes library research. Furthermore, it is analyzed using the content analysis method. The data sources used are journals, as primary data sources and other supporting books related to the object of research as secondary data sources. The results showed that the liquidity risk of Islamic banks is the same as other financial services. Liquidity risk is the risk resulting from the Bank's inability to fulfill maturing obligations from high-quality cash flow sources and/or liquid instruments that can be used as collateral, without disrupting the Bank's activities and financial condition. Therefore, estimating liquidity needs is complex. Banks must estimate liquidity needs and find ways to meet all funding needs in times of need. Bank liquidity needs come from two needs. Liquidity risk itself can be interpreted as the risk of the bank's inability to provide immediate liquidation at a fair price.